2019
DOI: 10.26434/chemrxiv.8159033
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Generic LC-MS/MS Exposome Method for the Determination of Xenoestrogens in Biological Matrices

Abstract: We are constantly exposed to a variety of environmental contaminants and hormones including those mimicking endogenous estrogens. These highly heterogeneous molecules are collectively referred to as xenoestrogens and hold the potential to affect and alter the delicate hormonal balance of the human body. To monitor exposure and investigate potential health implications, comprehensive analytical methods covering all major xenoestrogen classes are urgently needed but still not available. Herein, we describe an LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that complementary foods can be made from single or mixed cereals as a porridge, sometimes in combination with nuts, animal milk and other mashed items, and additional food groups are added as children get older (Alvito et al, 2010; Chuisseu Njamen et al, 2018; Kamala et al 2016; Kimanya et al, 2009, 2010, 2014; Ojuri et al, 2018, 2019). Unfortunately, in some parts of the world, some commonly consumed foods contain toxic fungal metabolites known as mycotoxins (Alvito et al, 2010; Braun et al, 2018; Cherkani-Hassani et al, 2016; Juan et al, 2014; Kamala et al, 2016; Kimanya et al, 2009, 2010, 2014; Chuisseu Njamen et al, 2018; Ojuri et al, 2018, 2019; Preindl et al, 2019; Warth et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that complementary foods can be made from single or mixed cereals as a porridge, sometimes in combination with nuts, animal milk and other mashed items, and additional food groups are added as children get older (Alvito et al, 2010; Chuisseu Njamen et al, 2018; Kamala et al 2016; Kimanya et al, 2009, 2010, 2014; Ojuri et al, 2018, 2019). Unfortunately, in some parts of the world, some commonly consumed foods contain toxic fungal metabolites known as mycotoxins (Alvito et al, 2010; Braun et al, 2018; Cherkani-Hassani et al, 2016; Juan et al, 2014; Kamala et al, 2016; Kimanya et al, 2009, 2010, 2014; Chuisseu Njamen et al, 2018; Ojuri et al, 2018, 2019; Preindl et al, 2019; Warth et al, 2016).…”
Section: Introductionmentioning
confidence: 99%